2008
DOI: 10.1007/s11136-008-9373-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring response shift in the quality of life of healthy adolescents over 1 year

Abstract: The findings support the assumption that the conceptualisation of QoL is stable during adolescence in the absence of significant health threats. However, researchers and clinicians should be aware of potential recalibration effects of some life domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…A recent crosssectional study on life satisfaction in German adolescents showed lower satisfaction in girls with a decrease in satisfaction for both genders from age 11 to 16 years [13]. However, another recent longitudinal study in England found a decrease only in physical health but not other HRQOL aspects in a cohort of adolescents over the course of 1 year [14].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent crosssectional study on life satisfaction in German adolescents showed lower satisfaction in girls with a decrease in satisfaction for both genders from age 11 to 16 years [13]. However, another recent longitudinal study in England found a decrease only in physical health but not other HRQOL aspects in a cohort of adolescents over the course of 1 year [14].…”
Section: Introductionmentioning
confidence: 93%
“…We used multilevel regression modelling allowing direct comparison of children and adolescents in different countries rather than within-country comparisons as in previous studies [13,14]. In contrast to previous studies that only analysed gender differences for a few specific age groups, we included children and adolescents from all ages between 8 and 18 years [3].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure has also been used to assess acute conditions such as back and fall injuries [24] as well as effects of treatment, such as dental implants [25], dermatological treatments [26], and knee surgery [27,28]. Finally, the thentest approach has been applied to the young [20,29,30], as well as to those nearing death [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, our scores appear to fit within the broad range of scores reported by previous studies. Previous studies which have used KIDSCREEN (or only its parent relation and home life dimension as we did) have found relatively small changes in these scores; however, the studies identified were all observational, [146][147][148] with the exception of Karasimopoulou et al 149 They used KIDSCREEN-52 with 10-to 12-year-olds in Greece as part of an evaluation of a health education/social skills programme (possible scores ranged from 6 to 30). The experimental group had a mean [± standard deviation (SD)] parent relation/home life score of 23.81 (± 6.46) before the intervention and 25.54 at follow-up (± 4.09).…”
Section: Effect Sizes Detected In Previous Studies (Secondary Outcomes)mentioning
confidence: 72%